Scientific Opinion on Analytical sensitivity of approved TSE rapid tests - EFSA Panel on Biological Hazards (BIOHAZ) (EFSA Journal)
Abstract The Community Reference Laboratory (CRL) for TSEs studied the analytical sensitivity for all the currently approved TSE rapid tests in order to produce robust analytical sensitivity data and evaluate each test against the same sample sets for the three main types of ruminant TSE: BSE, Classical scrapie and Atypical scrapie. This opinion provides a scientific evaluation of the CRL analytical sensitivity study, based on the requirements as set in the current EFSA protocols for the evaluation of TSE rapid post mortem tests. It is concluded that the CRL study findings provide valuable information in determining the continued suitability of tests currently used for TSE monitoring in the EU. Conclusions on the performance of the approved rapid tests within the CRL study are included. On these bases a number of tests cannot be recommended for use for the monitoring of BSE in cattle and TSE in small ruminants in the EU. Finally, the BIOHAZ Panel recommends that a similar study should be conducted with other types of TSE in cattle and small ruminants